A REVIEW ON EFFECTIVENESS OF TRICHODERMA SPP TO CONTROL BASAL STEM ROT DISEASE IN OIL PALM - Nor Dalia Nor Anuar; Intan Sakinah Mohd Anuar; Zaiton Sapak (Journal of Islamic, Social, Economics and Development, 2022)
Oil palm (Elaeis guineensis) is the primary agriculture industry in Malaysia.Currently, Malaysia ranks second in palm oil production after Indonesia. The one factor of oilpalm production decreasing is because disease infection. The major oil palm disease inMalaysia is Basal Stem Rot (BSR) that causes by Ganoderma boninense. BSR disease cancauses yield of oil palm production decrease in Malaysia. Various control approaches, such ascultural control, biological control, and chemical control, can be used to combat this diseasein oil palm. Nowadays, many companies or smallholders use chemical control to overcome BSRsuch as uses hexaconazole in application injection fungicides. However, chemical control cangive disadvantage to human health, especially to agricultural farmworkers that use chemicals.This review focus on uses of Trichoderma spp. as a biological control in controlling BSRdisease in oil palm because the implementation of biological control is more safe compared tothe use of chemical. This study review the effectiveness of biological control, which usesTrichoderma spp. and to review the factor efficiency that influencing Trichoderma spp. asbiological agent to control BSR disease. The finding shows the use of Trichoderma spp. asbiological control showed effective in terms of controlling the severity of BSR that affected tooil palm crop.